MALDIVIAN LEGAL SYSTEM: ISLAMIC INFLUENCE AND LEGAL REFORM - Ibrahim, Mohamed; Buang, Ahmad Hidayat (Jurnal Syariah, 2018)
The Maldivian legal system as it evolved, is one that has largely being influenced by the principles of Islam as a religion. With Islam declared to be the religion of the State in the Constitution, this is further strengthened by the fact that the Constitution mandates that no laws that are in contradiction to the tenets of Islam shall be ratified in the country. This sets the fundamental principle upon which the laws of the country rests. The reforms that have taken place since the enactment of the very first Constitution of the country in 1932 has in a large way being influenced by the said principle. Taking a qualitative approach, this paper aims to shed light on how Islam came to Maldives, the extent of its influence on the legal system in the country, and the scope for further studies on the subject.